KEBIJAKAN NEGARA PADA PENATAAN JARINGAN FIBER OPTIC DALAM MENDUKUNG KESUKSESAN PENYELENGGARAAN PERTEMUAN G20 DI BALI - Rijasa, I Wayan Suarka; Sutmasa, Yoseph Gede; Moedy, Emma Ratna Sari (Universitas Mahendradatta Denpasar, 2024)
Organizing the G20 meeting in Bali requires adequate infrastructure, including in terms of communication networks. Setting up a fiber optic network is one of the right solutions to meet these needs. This study aims to analyze state policies in structuring fiber optic networks as supporting infrastructure for the G20 meeting in Bali. The research method used is descriptive qualitative with data content analysis techniques. Data were obtained through interviews with informants regarding the policies for structuring fiber optic networks and also studying policy documents. The results of the study show that state policies in structuring fiber optic networks have been going well, but further efforts are still needed in the implementation process. Some of the obstacles faced in structuring fiber optic networks are inadequate regulations, insufficient suPPort from the private sector, and funding difficulties. Based on the results of this study, it is suggested that the government increase the number of regulations that support the arrangement of fiber optic networks, strengthen cooperation with the private sector, and seek more effective and efficient funding sources. With good state policies in structuring fiber optic networks, it is expected to suPPort the success of holding the G20 meeting in Bali.